Innovation as a Factor of Economic Development - Azizovna, Primova Azima (European Journal of Life Safety and Stability (2660-9630), 2022)
The relevance of the article is determined by the need to develop theoretical guidelines to increase the sustainability and efficiency of innovation-based industrial development, i.e. based on the knowledge economy. This is especially important in the context of limited economic resources and insufficient use of scientific and technological advances.